A cloud computing framework for sharing of cloud resources and attacks information amongst cloud networks - Waqas, Ahmad (Kulliyyah of Information and Communication Technology, International Islamic University Malaysia, 2016)
Cloud computing has emerged as a new paradigm for hosting and delivering computing resources over the Internet. This research proposed a cross-cloud communication framework (C3F) for enabling communication among clouds with minimal management burden. Further, it enabled the borrowing and lending of resources among clouds whenever required to fulfil the client requests. It also facilitated to share the information of attacks and intruding entities to cater with same attacks on different clouds. The framework was deployed using web-based prototype development to test and validate the cross-cloud communication. The prototype was developed using open source technologies. Moreover, algorithms were developed using low level description technique for the processes of resource borrowing and lending and, sharing of attacks information. The algorithms were analyzed to test their asymptotic running time complexity, and programmed in accordance with prototype of the study for testing and validation. The results showed high success rate of 94.4% for sharing of resources among clouds with mean allocation time of 12 microseconds. It was observed that 94.4% of the time clients' requests were fulfilled successfully after borrowing the resources from cloud network. An average of 100% results were collected for protecting multiple clouds from same attack by sharing the attacks and intruders information among clouds in different situations. It is therefore concluded that cross-cloud communication framework can benefit for sharing of resources and attacks information among clouds for efficient resource management and allocation and, protection against same attacks at different clouds.